KNOWLEDGE SHARING AND MULTI-CAMPUS UNIVERSITY SYSTEMS: GHANA’S UNIVERSITY FOR DEVELOPMENT STUDIES LIBRARY IN PERSPECTIVE - Bumbie-Chi, D. M. (UDS International Journal of Development, 2020)
This study was aimed at exploring knowledge sharing activities among library staff in a library that serves a multi-campus university in Northern Ghana. This study made use of quantitative research methods and a descriptive design. A questionnaire was used to gather data from the staff of the UDS Library across all campuses and was analyzed using IBM SPSS v23. The findings revealed that knowledge acquisition was mainly through workshops/ conferences/ seminars, personal development, in-service training, formal education and through colleagues. The knowledge sharing strategies identified included personal conversations, workshops/ training/ seminars, formal meetings, emails, telephone calls, chat groups and SMS. Challenges identified among staff on the same campus were apathy, grapevine communication, internet challenges and poor knowledge sharing culture among others. Across campuses, challenges related to distance, time, finances, irregular trainings and unhealthy competitions among others were identified. Keywords: Knowledge Sharing (KS), Multi-Campus University Systems (MCUS), Knowledge Sharing Strategies (KSS)